2023
DOI: 10.1038/s42003-023-04925-9
|View full text |Cite
|
Sign up to set email alerts
|

Fission yeast Srr1 and Skb1 promote isochromosome formation at the centromere

Abstract: Rad51 maintains genome integrity, whereas Rad52 causes non-canonical homologous recombination leading to gross chromosomal rearrangements (GCRs). Here we find that fission yeast Srr1/Ber1 and Skb1/PRMT5 promote GCRs at centromeres. Genetic and physical analyses show that srr1 and skb1 mutations reduce isochromosome formation mediated by centromere inverted repeats. srr1 increases DNA damage sensitivity in rad51 cells but does not abolish checkpoint response, suggesting that Srr1 promotes Rad51-independent DNA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Finding Skb1 RMTase targets is vital to elucidate how Skb1 causes isochromosome formation. Remarkably, skb1 and srr1 deletions additively reduce GCR rates [136], showing that Skb1 and Srr1 have nonoverlapping roles in GCR. In contrast to skb1, a srr1 mutation further reduces GCR rates in rad52-R45K mutant cells, suggesting a role of Srr1 in the Rad52-independent GCR pathway.…”
Section: Single-strand Annealing (Ssa) Causes Gcr At Centromeresmentioning
confidence: 97%
See 2 more Smart Citations
“…Finding Skb1 RMTase targets is vital to elucidate how Skb1 causes isochromosome formation. Remarkably, skb1 and srr1 deletions additively reduce GCR rates [136], showing that Skb1 and Srr1 have nonoverlapping roles in GCR. In contrast to skb1, a srr1 mutation further reduces GCR rates in rad52-R45K mutant cells, suggesting a role of Srr1 in the Rad52-independent GCR pathway.…”
Section: Single-strand Annealing (Ssa) Causes Gcr At Centromeresmentioning
confidence: 97%
“…Recently, it has been shown that Skb1/PRMT5 arginine methyltransferase (RMTase) and Srr1 play roles in isochromosome formation in the absence of Rad51 [136]. Mutation in the RMTase domain of Skb1 reduces GCR rates in rad51 deletion cells [136], showing that Skb1 causes isochromosome formation through RMTase activity. Skb1 regulates cell morphology and cell cycle progression, respectively, with Slf1 and Pom1 [192][193][194][195].…”
Section: Single-strand Annealing (Ssa) Causes Gcr At Centromeresmentioning
confidence: 99%
See 1 more Smart Citation